CRITERIA FOR PREDICTING RISKS IN THE CASE OF REPLACING AN EXTERNAL FIXATOR WITH AN INTERNAL FIXATOR DURING THE TREATMENT OF GUNSHOT FRACTURES OF THE EXTREMITIES - Burianov, Oleksandr; Yarmoliuk, Yurii; Derkach, Serhii; Gritsai, Mykola; Klapchuk, Yurii; Los, Dmytro; Omelchenko, Taras; Kolov, Gennady (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
In the treatment of victims with gunshot fractures of the long bones of the limbs, important importance is attached to determining the need and conditions for performing conversion (replacing the fixation method) with the formulation of reasoned indications. At the first stage of specialized care, such patients are fitted with external fixators, which provides adequate stabilization and simple wound care. Their conversion at the second stage to intraosseous increases the effectiveness of treatment. The aim: To analyze the results of using a scoring scale to substantiate the replacement of the fracture fixation method in the system of treatment of victims with combat limb injuries. Methods. The medical documentation for the period 2014-2021 was studied. The number of patients with gunshot fractures of long bones was 350, the average age was (36.4 ± 1.42) years. Patients were divided into two groups: the main group (193 wounded) — in the preoperative period, the authorʼs scale «Assessment of the possibility of conversion» was used; comparison (157 people) — point assessment was not performed. Methods. Descriptive, comparative analysis, systematic approach, statistical. The SF36 questionnaire was used to assess patients' quality of life. Results. The analysis of treatment results in the long term (1.2‒1.5 years) showed that the use of the author's scale in the preoperative period and the subsequent treatment made it possible to improve the subjective quality of life indicator by an average of 22.2 %. Conclusions. Justification of the expediency of replacing the fixation method during the treatment of patients with gunshot fractures of long bones using the developed scoring scale makes it possible to avoid unjustified conversion, reduce risks and minimize the occurrence of infectious complications.